Cladosporitides A–C, three polyketides from an endophytic fungi Cladosporium tenuissimum. (23rd November 2021) - Feng, Yaping; Liu, Wei; Li, Miaomiao; Ouyang, Yan; Yuan, Tao
Graphical abstract: Highlights: Three polyketides were isolated from an endophytic fungi Cladosporium tenuissimum . Cladosporitide A (1 ) possesses an unusual octahydro-2 H -2, 5-epoxychromene tricyclic structure moiety. Three polyketides exhibited moderate inhibitory activities against NO production in LPS-induced RAW 264.7 cells. Abstract: Three new polyketides, named cladosporitides A–C (1 –3 ), were isolated from an endophytic fungi Cladosporium tenuissimum derived from the stem of Berberis heteropoda . Their structures were determined by extensive spectroscopic analysis including HRMS, 1D and 2D NMR data. Compound 1 possesses an unusual octahydro-2 H -2, 5-epoxychromene tricyclic structure moiety. An anti-inflammatory assay indicated that compounds 1 –3 showed moderate inhibitory activities against LPS-induced NO production in RAW 264.7 cells with IC50 values ranging from 22.32 to 33.97 μM.